Agricultural technologies in India: A review - Joshi, Pramod Kumar; Varshney, Deepak (National Bank for Agriculture and Rural Development, 2022)
Agriculture sector in India is a primary source of livelihood for a majority of the population. Low and stagnant income in the sector remains a focal point of policy debate in India. The most prominent pathways to enhance farmers’ income is the adoption of improved agricultural technologies. This study documents the current state of agriculture technologies in India. The main objectives are: (a) What are the adoption levels of improved technologies and their impact on farmers’ income, agricultural production, natural resources and environment? (b) What are the constraints in up-scaling improved technologies and the conditions for success of their adoption? (c) What are the rate of return on agriculture research and extension system? and (d) What can be learnt from the global perspective on agriculture research and extension services?